Adolescent Idiopatic Scoliosis: A Literatur Review - Az-zahra, Falira Khoirunnisa; Fadila, Amila; Zahira, Lu’lu Al Fatina; Firdaus A, Abiel Dwi Cahya; Fadlurrohman, M. Zaidan; Anindya M, Nyoman Ayu; Aryuni, Baiq Aisha; Vaidika, I Komang Satya; Ramadhita, Nova Izza Salsa; Putra, Rian Akka Jaya; Akbar, Rauchan Abdi; Alaydrus, Muhammad Mukaddam (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2024)
Adolescent Idiopathic Scoliosis (AIS) is a structural spinal disorder commonly found in adolescents, characterized by an unknown cause of lateral curvature. This condition is typically detected during periods of rapid growth, particularly between the ages of 10 and 18. This literature review aims to provide a deeper understanding of adolescent idiopathic scoliosis in general, as well as to explore the latest management criteria for adolescent idiopathic scoliosis. The earlier AIS is detected and managed, the better the prognosis for the patient. The method used in this paper is a literature review. This review method involves searching for and examining reading Scholar, PubMed, and ProQuest regarding AIS. This paper summarizes the etiology, epidemiology, clinical manifestations, classification, diagnosis, and available treatments including management and rehabilitation currently available.